(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The article provides a brief historical overview of genus Epilobium s. l. It is one of the most complicated and species-rich genera within Onagraceae Juss. An important contribution to the study of the the genus in a broad interpretation and the development of infrageneric systems were made by Carl Linnaeus, Carl Haussknecht, Elizabeth Steinberg, Peter Hamilton Raven, Ilkka Kytövuori, Chia-Jui-Chen, David Baum, Naomi Grace Lorimer and Alexander Sennikov. We want to note among all these scientists Carl Haussknecht. He was first, who proposed the most perfectsystem of the genus Epilobium s. l. Also, Peter Raven one of the modern scientists made a very important contribution to the study of Epilobium s. l. taxonomy. He with co-authors proposed a system of the genus Epilobium s. l, which is based on the molecular phylogenetic analysis. Recently, other taxonomic criteria have been used for genus Epilobium L. s. l., as well as molecular phylogenetic data and traditional morphological features. These data allow to better understand anatomical, morphological and geographical characters of the species, their taxonomy and phylogenetic relationships. Species of genus Epilobium is in the stage of intensive formation, which causes difficulties in taxonomy. The presence a lot of forms within individual taxonomic units make borders between species blurred. Since there are unclear boundaries between species, there are difficulties in studying the taxonomy of the genus Epilobium s. l. The formation of hybrids of the genus Epilobium causes systematic complications in the study of this genus. In addition, today morphological data are insufficient to confirm the taxonomic status of the Chamaenerium species section. So an integrated approach to the study of the genus Epilobium s. l. is relevant today.